Life Lessons from the Fable “Nanthaka the Cow and the Lion King” (Nanthapakone) in the Lao version of “NangTanTai” Volume 1 (panchatanta) by Sila VILAVONGnta) by Sila VILAVONG - keomanyka, bounchan; KEOMANYKA, Bounchan (Souphanouvong University Journal Multidisciplinary Research and Development, 2025)
This article is a study of life lessons from the story “Nantaka the Cow and the Lion King” in the Lao version of “Nang Tantay” Volume 1 (Nanthakorn) translated by: Maha Sila Vilavong. This is qualitative research. The purpose is to analyze the life lessons that appear in the animal story through the actions and conversations of the characters. In this study, the researcher analyzed the characters in the story in depth by analyzing them according to the theory of character analysis of Sengfa Horanoupha. For data analysis, we used interpretation, verification, evaluation, and classification into each aspect. The study found that the life lessons from the fable "The Cow and the Lion" have a total of 67 messages divided into 3 areas: life lessons about qualities such as: gratitude, patience, responsibility for work, lessons about politics and society such as: knowing how to plan and evaluate the thoughts and feelings of subordinates, knowing how to weigh the benefits and harms of dividing work, in society there can be no good people - bad people, honest people - greedy people, and lessons about behavior - practice such as: lack of awareness, extravagance, improper actions will have great consequences.